Dyrektor szkoły - między opiekunem a kompetentnym zarządcą = The headmaster - between a caretaker and a competent manager - Prokosz, Małgorzata; Truhlářova, Zuzana (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This text is a pilot study with a small sample (N =57) addressing the quality of school work. It focuses on headmasters` opinions regarding their self-assessment of their preferred management and care strategies in the functioning of schools. On the one hand, the results indicate headmasters? preference for formal and legal choices in terms of strategies and, on the other hand, for formal and fragmented choices in terms of taking care, which may imply lower quality of work in schools. In order to con?rm this thesis, it is worth extending the ?eld of exploration to a larger research group, taking into account personality traits of the respondents, potential of the sta?, or material resources of particular institutions.
Keywords: dyrektor szkoły; jakość pracy; typy opiekuńczego funkcjonowania; kompetencje; osobowość; school headmaster; quality of work; types of caring; competences; personality